New Thoughts on Thought Disorders in Parkinson's Disease: Review of Current Research Strategies and Challenges - Jennifer G. Goldman (Parkinson's Disease)
Psychosis is a frequent nonmotor complication in Parkinson's disease (PD), characterized by a broad phenomenology and likely due to a variety of intrinsic (i.e., PD-related) and extrinsic factors. Safe and effective therapies are greatly needed as PD psychosis contributes significantly to morbidity, mortality, nursing home placement, and quality of life. Novel research strategies focused on understanding the pharmacology and pathophysiology of PD psychosis, utilizing translational research including animal models, genetics, and neuroimaging, and even looking beyond the dopamine system may further therapeutic advances. This review discusses new research strategies regarding the neurobiology and treatment of PD psychosis and several associated challenges.